Similarities of Lean Manufacturing Approaches Implementation in SMEs Towards The Success: Case Study in the Automotive Component Industry - A. N. M., Rose; M. F. F., Ab Rashid; N. M. Zuki, N. M.; Ahmad, H. (EDP Sciences, 2017)

(untitled)
Nowadays, manufacturing companies are striving for a better system like lean manufacturing (LM). The primary objective of LM is to identify and eliminate wastes. LM can be applied successfully in all industries providing a full understanding of lean ingredients i.e. concept, principles, and practices. There are a lot of practices which are necessary to be implemented in order to gain full benefits of LM. However, small and medium enterprises (SMEs) are lack of knowledge in LM and facing difficulties to adopt all of the LM principles. Therefore, it is necessary to the researchers to come out with a simple guideline for LM implementation. The objective of this paper is to explore the journey of LM implementation including preliminary, in process and post of LM. This research was conducted through multi-case study research. There were four SMEs and two large companies. The gathered information shows that the preliminary stage of LM implementation is similar to each other including large companies. The result shows SMEs still have a potential to success in LM. This finding might give an opportunity to SMEs to prepare the basis for LM implementation effectively. As a result, SMEs able compete in the competitive global marketplace and strive for world class performance through implementation of LM.